Analysis of Lien in Family Institution with Emphasizing on Insolvency of Husband - Abbas Ghasemi Hamed; Muhammad Ali Saeidi; Mostafa Shahbazi; Muhammad Ali Ghavami Nia; Ali Reza Matin Nia (آموزه‌‌های فقه مدني)
The civil law of Iran, considering jurisprudence, has predicted sanctions to prevent the breach of contractual liabilities. These sanctions are divided into two kinds of legal and contractual. Civil law doctrine of Iran has identified lien as one of the legal sanctions to prevent the breach of contractual liabilities. However, the title “contractual liabilities” has the primitive renunciation to financial liabilities, the legislator has identified the mentioned right as a guarantee mean in family institution. The main question of the present study is whether lien could play its role as a guarantee mean in family institution or not. By analyzing the linen characteristics, particularly in insolvency of husband and determining some of these characteristics of the mentioned right in recent condition, the result would be obtained that at least we can not consider this sanction in family if the husband is insolvent, however, there are doubts about the basis of this sanction in family institution. These doubts will be more severe by studying the main factors of desirable sanction and the negative consequences of “linen” in family, since it has some consequences in contrary to the family, so that this holy institution would be leaded to the lesion transaction which renders the family bases unsteady. This problem aggravates when the husband is insolvent. The issued question of this study has been deducted by the assistance of legal-jurisprudential logical analysis.